Substitüye Naftofuranların Sentezi - İstif, Mine (Fen Bilimleri Enstitüsü, 2016)
Bu çalışmada naftol türevleri ile glioksalbisülfit arasındaki reaksiyonlardan naftofuranonaftofuran bileşiğinin türevleri sentezlenmiştir. Naftofuranonaftofuran bileşikleri anti-kanser ve anti-AIDS özellikleri göstermektedirler. Daha önceleri grubumuz tarafından yapılan çalışmalarda sentezlenen yalın haldeki naftofuranonaftofuran bileşikleri A.B.D.’deki Kanser Enstitüsü tarafından incelenmiş ve ilaç aktivitelerinin düşük olduğu sonucu ortaya çıkmıştır. Bu sonuçtan yola çıkarak, naftofuranonaftofuran yapısına çeşitli gruplar, özellikle kanser ve AIDS’e karşı kullanılan ilaçların içerdikleri organik grupları takarak ilaç aktivitelerini arttırmak hedeflenmiştir. Öncelikle 2-naftol, 2,3-dihidroksinaftalen ve 2,7-dihidroksinaftalen ile glioksalbisülfit arasındaki reaksiyondan naftofuranonaftofuran ve dihidroksinaftofuranonaftofuran türevleri sentezlenmiştir. Daha sonra bu türevler üzerinden asetil, allileter ve brom grupları sübstitüye edilmiştir. Son aşamada allileter türevleri üzerinden Claisen Çevrilmesi ve asetoksi türevi üzerinden Fries Çevrilmesi uygulanmıştır.

In this work, naphthofuranonaphthofurans were synthesized via the condensation reaction between carbonyl compound (glyoxalbisulphid) and naphthols. Derivatives of naphthofuranonaphthofuran have anti-cancer and anti-AIDS properties. Some naphthofuranonaphthofurans, which were synthesized in our group before, have been tested for their potential anti-cancer and anti-AIDS properties at the National Cancer Institue, USA. However, none have shown encouraging biological activity. In this work, naphthofuranonaphthofuran compounds with new functional groups have been synthesized in order to increase their possible biological activities. Functional groups have been chosen from the compounds used for cancer and AIDS chemoteraphy. Firstly naphthofuranonaphthofuran and dihydroxy naphthofuranonaphthofurans were synthesized via the reaction between glyoxalbisulphid and 2-naphthol, 2,3-dihydroxynaphthalene, 2,7-dihydroxynaphthalene. Then, acetyl, allylether and bromine groups were substitued to naphthofuranonaphthofuran compounds. Also two rearrangments have been studied. Claisen Rearrangment was used for diallyloxy naphthofuranonaphthofuran. Fries Rearrangment has been worked for diacetoxy naphthofuranonaphthofuran.
Substitued Dinaphthofurano Derivatives
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1999
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1999
Keywords: Naftofuranonaftofuran; anti-kanser ve anti-AIDS; Naphthofuranonaphthofuran; anti-cancer and anti-AIDS